(untitled) (Jurnal Bina Praja, 2025)
The Pekanbaru City Population and Civil Registration Office adopts e-government through the Layanan Tunggu (Lagu) application to take care of lost, damaged, and urgent e-IDs. In practice, the Lagu application has not delivered good performance, as evidenced by the community satisfaction index, which consistently declined from 2021 to 2024. This study aims to analyse the performance and maturity of the Lagu application using the five dimensions of the balanced e-government scorecard and the stages of Darrell M. West’s e-government maturity model. The approach to this research is a qualitative descriptive design, using both primary and secondary data. The analysis technique of this study uses an interactive model by Miles, Huberman, and Saldana. The results of this study reveal that three of the five dimensions have not been operating optimally. Because iOS users can’t access the service, the removal of the urgent e-ID printing feature, the service of less friendly officers at the counter, the termination of the cooperation agreement with the Grab company, and the passive maintenance and development management of the application. In addition, the Lagu application, which experienced pseudo-maturity in the second stage, is another reason the public satisfaction index has consistently decreased. This research is limited to the object of research, namely the Lagu application, and does not include program recommendations. Therefore, the next research should examine collaborative governance and provide program recommendations based on the results.